Enhancement of fatigue endurance in ferroelectric PZT ceramic by the addition of bismuth layered SBT - Namsar,O. (American Institute of Physics Publising LLC, 2015)
© 2014 AIP Publishing LLC. Electrical fatigue properties of (1-x)PZT-xSBT ceramics (x = 0-1.0 weight fraction) were characterized. It was found that pure PZT ceramic had severe polarization fatigue. This was mainly attributed to an occurrence of the macroscopic cracks at near-electrode regions. On the contrary, pure SBT ceramic exhibited excellent fatigue resistance, which was attributed primarily to weak domain wall pinning. As small amount of SBT (0.1 ≤ x ≤ 0.3) was added into PZT, a small reduction of remanent polarization after fatigue process was observed. This demonstrated that these ceramics had high stability during the repeated domain switching due to their low oxygen vacancy concentration. Therefore, these results suggested that this new ceramic PZT-SBT system seemed to be an alternative material for replacing pure PZT in ferroelectric memory applications.